Violence in adolescents: social and behavioural factors Violencia en los adolescentes: factores sociales y conductas asociadas - Sandra Sousa; Teresa Correia; Elisabete Ramos; Sílvia Fraga; Henrique Barros (Elsevier, 2010)
Objective: To estimate the prevalence of young people's involvement in violence measured as participation in physical fights or being physically, sexually or emotionally abused. We also aimed to understand the role of social, demographic and other behavioural characteristics in violence. Methods: We evaluated 7511 adolescents (4243 girls and 3268 boys) aged 15 to 19 years old, enrolled in public schools. Information was obtained using an anonymous, self-administrated questionnaire. Results: The most frequently reported type of violence was emotional abuse (15.6%). Boys reported greater involvement in fights (3.6 vs. 13.6%, p<0.001) and physical abuse (7.5 vs. 19.5%, p<0.001). The prevalence of emotional abuse (16.2 vs. 14.8%, p=0.082) and sexual abuse (2.0 vs. 1.8%, p=0.435) was similar in girls and boys. After adjustment, increasing age decreased the odds of being involved in fights in both genders but increased the odds of emotional abuse. Living in a rented home was associated with physical abuse in girls (odds ratio [OR]: 1.4; 95% confidence interval [95%CI]: 1.0-1.9) and boys (OR: 1.6; 95%CI: 1.2-2.0). In girls the odds of being emotionally abused increased with greater parental education. Smoking and cannabis use were associated with all types of violence in both genders. Conclusions: The most frequently reported form of violence was emotional abuse. We found differences by gender, with boys reporting more physical abuse and involvement in fights. Adolescents whose parents had a higher educational level reported more physical and emotional abuse, which may be related to differences in the perception of abuse. Objetivo: Estimar la prevalencia de la participación de los jóvenes en peleas, y de ser físicamente, sexualmente o emocionalmente maltratados. Analizar la función de las características sociales, demográficas y de comportamiento sobre la violencia. Métodos: Se evaluaron 7.511 adolescentes (4.243 chicas y 3.268 chicos) de 15 a 19 años de edad, matriculados en escuelas públicas. La información se obtuvo por cuestionario anónimo auto-administrado. Resultados: La violencia emocional fue la más notificada (15,6%). Los chicos indicaron más peleas (3,6 frente a 13,6%, p<0,001) y maltrato físico (7,5 frente a 19.5%, p<0,001). La prevalencia de maltrato emocional (16,2% frente a 14,8%, p=0,082) y abuso sexual (2,0 frente a 1.8%, p=0,435) fue similar en chicos y chicas. Después del ajuste, en ambos sexos, la edad disminuye las probabilidades de participar en peleas, y aumenta las probabilidades de abuso emocional. Vivir en una casa alquilada se asoció con el abuso físico (odds ratio [OR]: 1,4 intervalo de confianza del 95% [IC95%]: 1,0-1,9) en las chicas y OR: 1,6; IC95%: 1,2-2,0 en los chicos. En las chicas la probabilidad de abuso emocional aumenta con la educación de sus padres. El tabaquismo y el consumo de cannabis se asociaron con todos los tipos de violencia, en ambos sexos. Conclusiones: La violencia con mayor prevalencia es la emocional. Encontramos diferencias por sexo, con los chicos notificando más abuso físico y participación en peleas. Los adolescentes cuyos padres tienen más educación indican más abuso físico y emocional, lo que podría estar relacionado con diferencias en la percepción de abuso.